2019
DOI: 10.1111/jftr.12324
|View full text |Cite
|
Sign up to set email alerts
|

Taking Care of Mine: Can Child Support Become a Family‐Building Institution?

Abstract: U.S. children are more likely to live apart from a biological parent than at any time in history. Although the Child Support Enforcement system has tremendous reach, its policies have not kept pace with significant economic, demographic, and cultural changes. Narrative analysis of in‐depth interviews with 429 low‐income noncustodial fathers suggests that the system faces a crisis of legitimacy. Visualization of language used to describe all forms child support show that the formal system is considered punitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 19 publications
0
20
0
Order By: Relevance
“…These strongly suggests that the government should ensure that all fathers, including those who were not married to the mother at the time of birth, should be afforded parenting time. In addition, shared custody should be the default for both married and unmarried parents, unless there is good cause not to do so (Edin et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These strongly suggests that the government should ensure that all fathers, including those who were not married to the mother at the time of birth, should be afforded parenting time. In addition, shared custody should be the default for both married and unmarried parents, unless there is good cause not to do so (Edin et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…This group is more often associated with racial/ethnic and economic disadvantage (Insabella, Williams, & Pruett, ; Waller & Dwyer Emory, ). Thus, these policies often treat less advantaged fathers as mere paychecks, and undervalue their role as involved parents (Edin, Nelson, Butler, & Francis, ).…”
mentioning
confidence: 99%
“…Historical accounts of early child support policy also highlight the centrality of this narrative, for example among activists of the National Organization of Women, important stakeholders in the early development of the system (Garfinkel, Meyer, & McLanahan, 1998). In many ways, child support enforcement was designed to require middle class, stably employed, absent fathers to “share the wealth” with their children (Edin et al., 2019; Sorensen & Lerman, 1997). Outcomes would thereby be more equitable (since mothers typically worked and earned far less).…”
Section: Family Policy and Policy Analysis: Some Families Count More Than Othersmentioning
confidence: 99%
“…In contrast to this gender‐equity‐focused narrative, many aspects of the child support system reflect a markedly different project: to require nonresident fathers to offset the costs of welfare payments to their children (Edin et al., 2019; Solomon‐Fears, 2016). While some mothers received welfare following divorce from relatively well‐off fathers, many fathers of low‐income children receiving welfare were themselves low income.…”
Section: Family Policy and Policy Analysis: Some Families Count More Than Othersmentioning
confidence: 99%
“…Sociology researchers (Edin et al, 2019), found that fathers who took an active fathering role with their children while still incarcerated were also more actively engaged in legitimate employment opportunities after release and less likely to become involved in illegal activities. Researchers note that the experiences of fathers in reconnecting and reestablishing a relationship with their children after a period of incarceration vary widely; however, there is compelling evidence that developing a positive connection with children and actively taking on a parenting role while incarcerated directly impacts the chances of success during the reentry phase of prisoner release and reintegration into the community (Boswell, 2018).…”
Section: Parenting Education and Reentry Successmentioning
confidence: 99%